The Muslims in Russia: between historical legacy and contemporary problematics. Issue 3 (2nd July 2016) - Abdel-Hafez Fawaz, Ahmed
ABSTRACT: Czarist Russia, the Soviet Union and Post-Soviet Russia had a history of relations with their Muslims that varied between integration or coexistence and resistance or conflict. Russia had perpetually reaffirmed that its war in Chechnya in the 1990s was not against Muslims per se, but rather against terrorist groups that were attempting to disseminate their radical ideas in the Muslim Chechen Republic as well as throughout the other republics of the North Caucasus. From their standpoint Chechen fighters described the struggle as a new round of Russian efforts to bury Chechen demands for independence. Nevertheless, this historical experience of struggle also coincided with periods of peaceful coexistence witnessed in other regions such as the Volga and Ural River Basin. Thus, the question remains: what of the contemporary challenges faced by the Muslims of Russia in their relations with the state and their relations among themselves? This research seeks to answer the following questions: How is it that religious and sectarian tolerance came to predominate in Tatarstan but regressed in Chechnya and Dagestan? Why have relations between Sufis and Salafists been subject to increasing tensions in the North Caucasus? Do the tensions witnessed in Dagestan and Chechnya reflect a genuine sectarian struggle or is the matter more complicated than that? How has the Russian media impacted – positively or negatively – ethnic and sectarian relations within the state?